Implementation Of Cooperative Learning In Engineering Education : A Case Study On The Utem Perodua Eco - Challenge Project - Mohd Tahir, Musthafah; Abdul Kudus, Syahibudil Ikhwan; Mansor, Muhd Ridzuan; Hassan, Muhammad Zahir; Shaharuzaman, Mohd Adrinata (2011)
Engineering education practice has evolved from traditional teacher centered learning to student centered learning in order to provide better understanding of the knowledge to the students in preparation towards job demands. One of the approach in student centered learning is the cooperative learning technique. In this paper, the implementation of cooperative learning technique to students from Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka which participated in the 2011 Perodua Eco- Challenge competition arc discussed. Both formal and informal cooperative learning approaches were applied during the project which consists of a group of students with diverse Ievel of knowledge and skills. The effectiveness of the technique was measured in term of project outcome and survey on the participant feedbacks. Limitations of this technique were also highlighted wit11 several recommendations included to better improve on the delivery of the active learning technique for similar project in the future.